Suppression of malignant neoplasms in biological structures by method of immune therapy - Dovbnya, A.N.; Yefimov, V.P.; Kramskoy, G.D. (Вопросы атомной науки и техники, 2017)
An approach to solve a problem of reducing the zone of malignant tumors in biological structures is proposed. The method is based on the combined effect of permanent magnetic and electric fields on the vascular endothelium of the blood stream in biological structures in order to enhance the immune response in the body. Monitoring of the state of the area under treatment is carried out by resonant diagnostics in the UHF band.